Sudden Cardiac Death in Patients With Ischemic Heart Failure Undergoing Coronary Artery Bypass Grafting: Results From the STICH Randomized Clinical Trial (Surgical Treatment for Ischemic Heart Failure). Issue 12 (21st March 2017) - Rao, Meena P.; Al-Khatib, Sana M.; Pokorney, Sean D.; She, Lilin; Romanov, Alexander; Nicolau, Jose C.; Lee, Kerry L.; Carson, Peter; Selzman, Craig H.; Stepinska, Janina; Cleland, John G.F.; Tungsubutra, Wiwun; et al.
Abstract : Background: The risk of sudden cardiac death (SCD) in patients with heart failure after coronary artery bypass graft surgery (CABG) has not been examined in a contemporary clinical trial of surgical revascularization. This analysis describes the incidence, timing, and clinical predictors of SCD after CABG. Methods: Patients enrolled in the STICH trial (Surgical Treatment of Ischemic Heart Failure) who underwent CABG with or without surgical ventricular reconstruction were included. We excluded patients with prior implantable cardioverter-defibrillator and those randomized only to medical therapy. The primary outcome was SCD as adjudicated by a blinded committee. A Cox model was used to examine and identify predictors of SCD. The Fine and Gray method was used to estimate the incidence of SCD accounting for the competing risk of other deaths. Results: Over a median follow-up of 46 months, 113 of 1411 patients who received CABG without (n = 934) or with (n = 477) surgical ventricular reconstruction had SCD; 311 died of other causes. The mean left ventricular ejection fraction at enrollment was 28±9%. The 5-year cumulative incidence of SCD was 8.5%. Patients who had SCD and those who did not die were younger and had fewer comorbid conditions than did those who died of causes other than SCD. In the first 30 days after CABG, SCD (n=5) accounted for 7% of all deaths. The numerically greatest monthly rate of SCD was in the 31- to 90-day time period. In a multivariable analysis including baseline demographics, risk factors, coronary anatomy, and left ventricular function, end-systolic volume index and B-type natriuretic peptide were most strongly associated with SCD. Conclusions: The monthly risk of SCD shortly after CABG among patients with a low left ventricular ejection fraction is highest between the first and third months, suggesting that risk stratification for SCD should occur early in the postoperative period, particularly in patients with increased preoperative end-systolic volume index or B-type natriuretic peptide. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT0002359.